Healthcare resource utilization and costs among children with cystic fibrosis in the United States. Issue 9 (7th July 2021) - Thorat, Teja; McGarry, Lisa J.; Bonafede, Machaon M.; Limone, Brendan L.; Rubin, Jaime L.; Jariwala‐Parikh, Krutika; Konstan, Michael W.
Abstract: Background: Adverse health impacts of cystic fibrosis (CF) can be present in children before respiratory complications are observed. Children with CF show progressive health decline, with increasing lung function decline in adolescence. This study aims to quantify the healthcare resource utilization (HCRU) and costs attributable to CF by comparing children with CF with the general pediatric population. Methods: This retrospective, cross‐sectional, observational study compared HCRU and costs among children with CF in the US with demographically similar children without CF (comparison group) over a 12‐month period using administrative claims data spanning 2010–2017. Analyses were conducted by insurance type (commercially insured [COM] and Medicaid insured [MED]) and stratified by age (<2 years, 2 to <6 years, 6 to <12 years, and 12–17 years). Results: Children with CF (2831 COM and 1896 MED) were matched to children in the comparison group (8493 COM and 5688 MED). Higher prevalence of comorbidities was seen in children with CF versus the comparison group across all ages. Across all ages, HCRU attributable to CF was substantial (higher hospitalization rates, more outpatient and emergency room visits, and greater use of prescription medications), and there were higher associated costs (all p values < .05), in COM and MED populations. HCRU and costs attributable to CF were highest for children aged 12–17 years. Conclusions: Substantial HCRU and costs are evident among children with CF across all ages, starting as young as infancy, with highest HCRU and costs among adolescents. Effective treatments from an early age are needed for children with CF.